Experimental evaluation of influence of temperature on nature of fracture in formability test of alpha-beta titanium alloy. (2020) - Shukla, Anoop Kumar; Mohandas, T.
Highlights: Graphite grease proved better lubricant than silicone oil during formability test. Blank thickness has maximum contribution for warm temperature deformation. Optimized process parameters have shown the maximum formability. Temperature of formability test influenced the fracture mode during the deformation. Abstract: In the present era, titanium alloys are the workhorse in aeronautical component production applications. The formability tests are carried out for alpha-beta titanium alloy sheet metal blanks using the Erichsen Cupping Test, under the different tribological conditions and at varying temperatures. Taguchi Method of optimization technique is used to optimize the process parameters and analysis of variance is also carried out to obtain percentage contribution of each parameter. The various forming conditions at different temperatures involved a varying range of stress. The fractures occurred after necking during formability test. Further these fractures are analyzed for their nature. The paper aims to disseminate the research highlights from a research project sanctioned from Science and Engineering Research Board, Directorate of Science and Technology, Govt. of India, vide file no. EMR/2016/007303 dated 20 Mar 2018.